CHRONOLOGY OF THE TIME OF THE NARRATIVE DISCOURSE IN THE NOVEL – GAHISHTINEKA WAKI MIRNE - SALIH, MOHSIN ARIF; AHMED, DILDAR IBRAHIM; GAZI, CHINAR SADIQ (Journal of Duhok University, 2020)
Since ancient times, man has struggled with time, in order to organize his life and overcome the obstacles of life, so he has always resorted to glorifying events and experiences that happened to him in order to record his heroism in order to become a solid motivation for him to advance in the future, without any doubt the narration of events has a feature or a chronological featureof his three temporal verbs (past, present, future). This is why time has become an important topic, as many scholars and critics have undertaken studies in order to determine the sequence and chronological organization in the historical and literary fields.Novel as a narrative genre took time as an artistic feature of a fundamental role in the field of narration, and therefore time took a place especially in the field of novel writing, while when (Gerard Genet) studied the novel from the chronological aspect of the story in the narrator’s speech and the events of the novel according to the recognized chronological organization, he reached a stage It is developed in the analysis of narrative discourse, making the novel a part of the double time (the time of the story and the time of the speech) with three levels (order, duration, frequency) and this by determining the real time or referring to it. This research is an attempt to define the chronology of the narrative discourse under the title (Chronology of the Time of the Narrator's Speech in the Novel Gahishtineka waki mirne). According to the opinions of (Gerard Genet).